1991
DOI: 10.1104/pp.97.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Gibberellin A12 and A12-Aldehyde in Developing Seeds of Pisum sativum L.

Abstract: Metabolism of [14C]gibberellin (GA) A12 (GA12) and [14C]gibberellin A12-aldehyde (GA12-aldehyde) was examined in cotyledons and seed coats from developing seeds of pea (Pisum sativum L.). Both were metabolized to only 13-hydroxylated GAs in cotyledons but to 13-hydroxylated and non-13-hydroxylated GAs in seed coats. appropriate markers for the recovery of endogenous GAs from seed coats or cotyledons. These GAs were purified by HPLC and identified and quantified by gas chromatography-mass spectrometry. GA15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The presence of the GA 9 metabolites was not caused by the presence of added GA 9 , as the endogenous GAs were identified from non-treated tissue . The endogenous levels of GA51 and GA51 -catabolite in seed coats were much higher than GA 9 [24] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of the GA 9 metabolites was not caused by the presence of added GA 9 , as the endogenous GAs were identified from non-treated tissue . The endogenous levels of GA51 and GA51 -catabolite in seed coats were much higher than GA 9 [24] .…”
Section: Discussionmentioning
confidence: 97%
“…The endogenous level of GA9 per shoot (allowing for the usual 50% recovery) was about 6.4 pmol/shoot, so that the applied GA 9 was about 12 times the endogenous concentration, and the endogenous level in seed coats was 8.7 ng/g [24] as compared to the fed amount of 15 ng/g, almost twice the endogenous level . Nonetheless the amount fed was still much lower than that supplied in other quantitative studies with intact pea seeds [7], which was 300 ng/g at the lowest and 9 .8µg/g at the highest level .…”
Section: Discussionmentioning
confidence: 99%
“…A corollary is that GA20 deactivation is a regulated process in the garden pea, a suggestion consistent with previous observations. For example, the step GA29 to GA29-catabolite, in particular, proceeds much faster in some organs than in others (Sponsel, 1983;Zhu et al, 1991), and GA20 2~-hydroxylase activity has been shown to vary with time in developing pea seeds (Smith and MacMillan, 1986). It has been suggested also that in Phaseo/us vulgaris seeds the metabolism of GA20 is under regulatory control (Albone eta/., 1989).…”
Section: Discussionmentioning
confidence: 99%
“…These products do not appear to be catabolized further, at least in pea (Ingram et a/., 1985), and, consequently, they accumulate to very high levels in certain organs (Ingram et al 1985;Sponsel, 1983). It appears that in the maturing seed, 2~-hydroxylation of GA20 can occur in both cotyledons and testa, while the step GA29 to GA29-catabolite is restricted mainly to the testa (Sponsel, 1983;Zhu et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…20 d after anthesis), as before (Zhu and Davies 1991;Ross et al 1995). The substrate (500 ng in 25 lL distilled water) was fed to genotype lh-2, for 24 h.…”
Section: Methodsmentioning
confidence: 99%